Prenatal Risk Factors for Adverse Developmental Outcome in Preterm Infants—Systematic Review - Ylijoki, Milla K.; Ekholm, Eeva; Ekblad, Mikael; Lehtonen, Liisa (Frontiers in Psychology, 2019)
Background Preterm infants are still at an increased risk for suboptimal neurodevelopmental outcomes when compared with term born infants. The development of a child born preterm can be jeopardized by suboptimal conditions during pregnancy, in addition to the suboptimal growth environment postnatally compared to the normal in utero environment. This review summarizes the literature on the role of chorioamnionitis, placental insufficiency, and maternal smoking on the developmental outcomes of preterm infants. Methods A systematic database search was performed to identify all original articles published on or before September 12, 2018 that evaluated the impact of clinical or histological chorioamnionitis, abnormal antenatal prenatal fetal and placental blood flow, and prenatal smoking exposure on the neuropsychological and cognitive outcomes of preterm infants. We identified a total of 54 studies. Thirty five original articles evaluated the effects of clinical or histological chorioamnionitis; 15 studies evaluated the effects of abnormal blood flow patterns; and four studies evaluated the effects of maternal smoking during pregnancy. Results The studies on antenatal prenatal risk factors showed conflicting results about the impact on the neurodevelopment of preterm infants. The majority of the studies did not show that chorioamnionitis poses a direct risk to the development of preterm infants. The role of abnormal antenatal prenatal placental and fetal blood flow on the development of preterm infants remained inconclusive because the sample sizes were often small and methodological problems complicated the interpretation of the data. Maternal smoking during pregnancy was assessed only in one cohort which showed that maternal smoking is a risk for suboptimal cognitive and neuropsychological development in preterm infants. Conclusions This review summarizes the data on several antenatal prenatal risk factors which play a role in the developmental outcomes of preterm infants. To optimize the developmental outcomes, we need to first optimize the fetal wellbeing before birth. More research that extends from the fetal life to long-term developmental outcomes is needed.